Social Media as a Catalyst for the Enhancement of Destination Image: Evidence from a Mediterranean Destination with Political Conflict - Farhangi, Sanaz; Alipour, Habib (Mdpi, 2021)
Digitalization-oriented transformation provides enormous possibilities to all sectors, ranging from manufacturing to the service industries. This study aimed to investigate the role of social media and its utilization by tourism operators/policymakers as a catalyst to enhance the image of a destination that is grappling with political deadlock and burdens of nonrecognition despite its abundance of tourism resources. The case of north Cyprus is an embodiment of a number of destinations that are challenged by political hurdles, conflicts, and nonrecognition, which result in economic hardship, political uncertainty, and social disappointment. This research aimed to investigate the role of social media in popularizing and marketing north Cyprus by placing it on the global digital tourism map. For the purpose of this study, a qualitative research method was employed and data collected through semi-structured interview questions. The interviewees were mainly public sector tourism officials, hoteliers, travel agency managers, and tourism academicians. Data analysis was conducted by applying Atlas.ti 9 (1.0.0.206) software. The findings reveal that tourism operators and policymakers have failed to take advantage of social media platforms-which have become a form of public goods-to mitigate the negative effects of the political impasse that has curtailed the tourism sector. The implications and contributions are also discussed.
Keywords: social media platforms; destination image; tourism; political deadlock; north Cyprus